Alimentos ultraprocessados e mortalidade entre indivíduos brasileiros em prevenção secundária de doença cardiovascular: Projeto DICA Br - Rocha, Bárbara Rafaela Santos da (2020)
Background: Ultra-processed foods (UPF) give poor quality to the diet due to the imbalance and unavailability of nutrients, food additives and contaminants with carcinogenic potential. The consequences of their increasing participation in the diet are the increase in metabolic and cardiovascular diseases, which are mainly responsible for premature deaths in the world. Objectives: To investigate the association between UPF consumption and mortality among Brazilian individuals in secondary prevention of cardiovascular diseases. Secondarily, we seek to identify the relationship between UPF, socioeconomic determinants of health and dyslipidemia as a factor of atherosclerotic cardiovascular risk. Methods: The present study evaluated 1931 participants of the Brazilian Cardioprotective Nutritional Program (Balance Program) aged over 45 years, diagnosed with established cardiovascular disease, recruited between 2013 and 2017 and follow up for 3.8 years. Demographic data, disease diagnoses, clinical measurements, anthropometric, biochemical parameters, socioeconomic, dietary and mortality information were collected. Dietary information was collected through two 24-hour recall (R24h) and food consumption was categorized according to the extent and purpose of food processing, proposed by the NOVA Classification. A systematic review of the literature was also performed to support the management of socioeconomic variables in this study and its relationship with ultra-processed foods. Results: A systematic review included18 studies, totaling 68,373 individuals. The results showed that better economic and educational conditions are risk factors for UPF consumption in developing countries, while in developed countries they are protective factors. To verify the findings of the systematic review, we conducted an observational cross-sectional study in this sample, which sought the effect of socioeconomic factors in determining UPF consumption. In multivariate linear regression analysis, it was found that UPF consumption was higher in regions with a higher human development index (HDI), and also showed interaction between economic and educational factors on consumption. Thus, in the high HDI region (Southeast), the upper-middle class tended to decrease the consumption of UPF with the increase in schooling. While in the region with the lowest HDI (Northeast), the middle class increased the consumption of AUP with the increase in educational level. Then, we started to associate UPF with the risk of dyslipidemia and the role of socioeconomic factors in this relationship. After performing multivariate logistic regression, the consumption of 10% of energy from UPF increased the odds ratio of dyslipidemia by 17%. This effect was enhanced by the better socioeconomic conditions of the individuals and the region of residence. Finally, we constructed prospective analyzes, using multivariate Cox regression, which associated the energy contribution of 1% of ultra-processed foods to a 17% increase in the risk of cardiovascular mortality. Greater internal consistency of the results was observed with the increase in the schooling of individuals in the middle class. Conclusion: In short, a high risk of cardiovascular mortality was found associated with an increased contribution of ultra-processed foods to the diet among individuals with cardiovascular diseases. Although the consumption of AUP is more prevalent in better economic conditions, which increases the chances of dyslipidemia in these strata, it is among the middle-class that there is a higher incidence of mortality.